Graphene/TiO2 decorated N-doped carbon foam as 3D porous current collector for high loading sulfur cathode. (March 2021) - Xia, Yang; Ren, Qiang; Lu, Chengwei; Zhu, Jing; Zhang, Jun; Liang, Chu; Huang, Hui; Gan, Yongping; He, Xinping; Zhu, Dongmin; Xiao, Zhen; Zhang, Wenkui
Graphical abstract: Highlights: G/T-NF@CNT foam skeleton acts as current collector to thick sulfur cathode. NF@CNT conductive framework guarantees excellent electrical contact to sulfur. N-doping carbon skeleton and G/T modified layer effectively anchor polysulfides. G/T-NF@CNT/S cathode has high areal capacity and superior cycling stability. Abstract: The intrinsic contradiction between high loading and high capacity in sulfur cathode severely limits the commercial viability of Li-S batteries. Herein, Graphene/TiO2 decorated N-doped carbon foam (G/T-NF@CNT) is proposed as three-dimensional (3D) current collector for high loading sulfur cathode. This rationally designed current collector can not only provide enough space to accommodate active sulfur, but also endow sulfur cathode with strong polysulfide confining ability. More interestingly, 3D porous conductive structure has sufficient channels to realize rapid mass mobilization; meanwhile the high conductivity networks boost transfer kinetics of electrons. The electrochemical measurements demonstrate that G/T-NF@CNT/S cathode has a remarkable capacity of 788 mA h g −1 (5.83 mA h cm -2 ) at 0.1 A g −1 after 100 cycles with a high sulfur loading of 7.4 mg cm -2 . This work provides new insights on multifunctional current collectors for thick sulfur cathodes in Li-S batteries.